The Knee Joint Surgical Techniques and Strategies - Bonnin, Michel; Amendola, Ned Annunziato; Bellemans, Johan; MacDonald, Steven J.; Menetrey, Jacques (Springer Paris : Imprint: Springer, 2012)
Pushed by the progress of biology, technology and biomechanics, knee surgery has dramatically evolved in the last decades. This book is a "state of the art" concerning all aspects of knee surgery from ligament reconstruction to Total Knee Arthroplasty. An international panel of renowned authors have worked on this didactic fully illustrated book. It will help young surgeons to understand basic sciences and modern sugical techniques. The experienced surgeon will find help to deal with difficult cases and clarifications in recent technologic advances such as cartilage surgery, navigation and mini invasive surgery.